Game Edukatif Make a Match: Solusi Inovatif untuk Meningkatkan Hasil Belajar Matematika di Sekolah Dasar - Surya Widyasari; Zulqoidi R. Habibie; Elvima Nofrianni (CV. Master Literasi Indonesia, 2025)
This study is driven by the learning process that does not yet align with the requirements of the Independent Curriculum, along with students' low academic achievement. The study is centered around the following research concern